Dictatorland : the men who stole Africa - Kenyon, Paul, 1966-; Edwards, Jeff (London : Head of Zeus Ltd, 2018)
"The dictator who grew so rich on his country's cocoa crop that he built a 35-story-high basilica in the jungles of the Ivory Coast. The austere, incorruptible leader who has shut Eritrea off from the world in a permanent state of war and conscripted every adult into the armed forces. In Equatorial Guinea, the paranoid despot who thought Hitler was the savior of Africa and waged a relentless campaign of terror against his own people. The Libyan army officer who authored a new work of political philosophy, The Green Book. And behind these almost incredible stories of fantastic violence and excess lie the dark secrets of Western greed and complicity, the insatiable taste for chocolate, oil, diamonds and gold that have encouraged dictators to rule with an iron hand, siphoning off their share of the action into mansions in Paris and banks in Zurich and keeping their people in dire poverty"--
Introduction -- Part One: Gold and diamonds. Congo ; Zimbabwe -- Part Two: Oil. Before the dictators ; Libya ; Nigeria ; Equatorial Guinea -- Part Three: Chocolate. Before the dictators ; Côte d'Ivoire -- Part Four: A modern slavery. Eritrea.
Map on lining papers.
Includes bibliographical references (pages 431-441) and index.
Keywords: Dictatorship -- Africa; Dictatorship -- Economic aspects -- Africa; Political leadership -- Africa; Africa -- Politics and government -- 1960-